STRATEGI PONDOK PESANTREN DALAM MENANAMKAN NILAI KEPEDULIAN SOSIAL MELALUI BUDAYA GOTONG ROYONG DAN BANTUAN INFAQ (Studi Kasus Di Pondok Pesantren Putri Walisongo Cukir Jombang) - Asmaul Fauzi, Aziza; Said, Ali (EL-Islam, 2023)
Abstract: In indonesia, showing the value of social concern shows a declining symptorn caused by the develpment of technology and the internet, especially with the presence of smartphones that make people become morally narrow. Being less sensitive adn indifferent to the surrrounding environment makes a person an individualistic personality. With pesantren education, santri are taught and guided to have an attitude of helping each other, helping other (berinfaq), kinship, empathy and tolerance. The objectives that will be studied The study's aims will be as follows: (1) To describe strategy of Islamic boarding schools in instilling the importance of social care a culture of the mutual cooperation and infaq assistance ]and (2) to identify the elements that aid and hinder Islamic boarding schools in implementing a culture of mutual cooperation and infaq assistance for female students Walisongo Cukir Jombang. This research blends descriptive research with a qualitative approach. Techniques for gathering data include observation, interviews, and documentation. Techniques for data analysis include data reduction, data display, and verification. And to check the data's authenticity, use (1) credibility: a. improved persistence, b. observational extension, c. triangulation, (2) transferability, (3) dependability, (4) confirmability. The results of the research show that: 1) The administrators at the Islamic Boarding School of Walisongo Cukir Jombang in instilling the value of social care to students applying habituation patterns, and reguiring students to follow and help other students and fostering a sense of togetherness in carrying out the cleaning picket schedule. Factors in favor of the pondok in instilling a culture of mutual cooperation and infaq assistance at the Islamic Boarding School of Walisongo Cukir Jombang School include: a). there is direct control from the chairman of the pondok, b). the active role of complex administrators and supervisors, c). existence of facilities that support these activities, d). there is cohesiveness between the management and the supervisor and the students, d). motivation and exemplary examples from parents and administrators. Mean while, the inhibiting factors The following are the benefits of Islamic boarding schools in establishing the value of social caring in students: pupils' lack of understanding about the significance of social care to pupils is, kids' lack of awareness about the necessity of assisting and caring.